2023
DOI: 10.1073/pnas.2220552120
|View full text |Cite
|
Sign up to set email alerts
|

Microsaccades are directed toward the midpoint between targets in a variably cued attention task

Abstract: Reliable, noninvasive biomarkers that reveal the internal state of a subject are an invaluable tool for neurological diagnoses. Small fixational eye movements, called microsaccades, are a candidate biomarker thought to reflect a subject's focus of attention [Z. M. Hafed, J. J. Clark, VisionRes. 42 , 2533–2545 (2002); R. Engbert, R. Kliegl, VisionRes. 43 , 1035–1045 (2003)]. The linkage between the direction of microsaccades and attention h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Saccade preparation is another factor which can modulate the low-frequency oscillations in V4 (Steinmetz and Moore, 2014) that might contribute to better behavioral discriminability. However, a recent study which used the same experimental data found no difference in the microsaccade direction – a potential indicator of saccade preparation (Hafed and Krauzlis, 2012) - between hits and miss trials (Willett and Mayo, 2023).…”
Section: Discussionmentioning
confidence: 93%
“…Saccade preparation is another factor which can modulate the low-frequency oscillations in V4 (Steinmetz and Moore, 2014) that might contribute to better behavioral discriminability. However, a recent study which used the same experimental data found no difference in the microsaccade direction – a potential indicator of saccade preparation (Hafed and Krauzlis, 2012) - between hits and miss trials (Willett and Mayo, 2023).…”
Section: Discussionmentioning
confidence: 93%
“…A recent study (Willett & Mayo, 2023) found little to no evidence for a directional biasing of microsaccades to an attended visual stimulus, despite clear behavioural and neural benefits of attention. A critical difference with our study is that the authors did not consider shifts of attention following a cue, but rather sustaining attention to either of two targets that remained fixed throughout a block of trials.…”
Section: Discussionmentioning
confidence: 98%
“…One particular example of this contribution comes from the study of microsaccades, a class of fixational eye-movements that occur even during attempted fixation (e.g., (Engbert, 2006;Hafed et al, 2015;Martinez-Conde et al, 2004;Rolfs, 2009;Rucci & Poletti, 2015)). In particular, it has been demonstrated how the direction of fixational microsaccades can be modulated by the deployment of spatial attention to peripherally attended locations, in the absence of large eye-movements to these locations ( (Corneil & Munoz, 2014;Engbert, 2012;Engbert & Kliegl, 2003;Fernández et al, 2023;Hafed et al, 2011;Hafed & Clark, 2002;Laubrock et al, 2005;Lowet et al, 2018;Pastukhov & Braun, 2010;Xue et al, 2020); but see also (Horowitz et al, 2007;Tse et al, 2002;Willett & Mayo, 2023) to which we return in our discussion). Building on this earlier work, we recently uncovered similar microsaccade biases when directing attention to memorised visual contents held within the spatial lay-out of working memory (e.g., (de Vries & van Ede, 2023;Liu et al, 2022;van Ede et al, 2019van Ede et al, , 2020van Ede et al, , 2021).…”
Section: Introductionmentioning
confidence: 92%
“…Attention shifts induced by emotional stimuli modulated microsaccadic activity ( Kashihara et al, 2014 ). In more ecologically valid environments, some studies replicated the link between attention and microsaccade direction (e.g., Barnhart et al, 2019 ; Xue et al, 2020 ), while others found that this relationship disappears with increasing environmental complexity ( Willett and Mayo, 2023 ).…”
Section: Microsaccade Direction and Attention Shiftsmentioning
confidence: 97%